Intraoperative Floppy Iris Syndrome: Updated Perspectives - Christou CD (Dove Medical Press, 2020)
Chrysanthos D Christou,* Ioannis Tsinopoulos, Nikolaos Ziakas, Argyrios Tzamalis* 2nd Department of Ophthalmology, Aristotle University of Thessaloniki, Papageorgiou General Hospital, Thessaloniki, Greece*These authors contributed equally to this workCorrespondence: Argyrios Tzamalis 2nd Department of Ophthalmology, Aristotle University of Thessaloniki, Papageorgiou General Hospital, Thessaloniki, GreeceTel +30 69 4206 0467Fax +30 23 1332 3974Email argyriostzamalis@yahoo.comAbstract: Almost fifteen years since its initial description, intraoperative floppy iris syndrome (IFIS) during phacoemulsification surgery remains a challenge for cataract surgeons in all its key aspects that include the stratification of the preoperative risk, preoperative prophylaxis treatment, surgery design and intraoperative management. Since its original association with tamsulosin intake, IFIS has been positively correlated with a plethora of risk factors which include: gender, age, hypertension, other a1-adrenergic receptor antagonists, finasteride, angiotensin II receptor inhibitors, benzodiazepines, antipsychotics, hypertension drugs and decreased dilated pupil diameter. The assessment and stratification of the preoperative risk is pivotal in screening patients prone to develop IFIS. For these patients, it is essential that preoperative prophylaxis, employment of necessary measures and surgical technique modifications are considered. A multidisciplinary approach of IFIS is a mandate, thus ophthalmologists, urologists and sometimes other specialties should cooperate to “educate” each other about the risks of their respective fields. They both must be aware of the joint statement on IFIS by the American Academy of Ophthalmology and the American Society of Cataract and Refractive Surgery which suggests either the initiation of tamsulosin after phacoemulsification or the use of a non-selective a1-ARA for benign prostatic hyperplasia treatment. In conclusion, awareness of the risk factors associated with IFIS and their detailed preoperative documentation is crucial in addressing IFIS. The lack of such an awareness can turn a routine, uneventful surgery into one with significant visual morbidity.Keywords: intraoperative floppy iris syndrome, IFIS, risk factors, preoperative prophylaxis, intraoperative management